2018
DOI: 10.3386/w25044
|View full text |Cite
|
Sign up to set email alerts
|

ICT, R&D and Organizational Innovation: Exploring Complementarities in Investment and Production

Abstract: Robin, Nicolas van Zeebroeck, and the participants at various workshops. Errors are our own. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
(51 reference statements)
3
14
0
Order By: Relevance
“…Furthermore, in the case of firms in services, productivity returns to investment in R&D are enhanced by investment in software. This result is consistent with recent evidence on complementarities between investments in R&D and information and communication technologies provided by Corrado et al (2017) and Mohnen et al (2018).…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, in the case of firms in services, productivity returns to investment in R&D are enhanced by investment in software. This result is consistent with recent evidence on complementarities between investments in R&D and information and communication technologies provided by Corrado et al (2017) and Mohnen et al (2018).…”
Section: Resultssupporting
confidence: 93%
“…Contrary to findings by Ding et al (2010) and Kleis, Chwelos, Ramirez, and Cockburn (2012), we find a weak relationship between ICT and R&D, this is consistent with Mohnen, Polder, & van Leeuwen (2018) who posit that there is a weak link between ICT and R&D as inputs to innovation. This phenomenon could be due to the inability of developing countries to utilize the full economic value of ICT facilities at their disposal.…”
Section: Discussionsupporting
confidence: 70%
“…Other scholars have highlighted the role of ICT in the innovation process, making strong arguments that ICT is a significant driver of innovation (Kretschmer, 2012;Hue, 2019;Idota, Bunno, & Tsuji, 2020). However, literature seldom considers the role of ICT next to R&D (Mohnen, Polder, & van Leeuwen, 2018). Venturini (2015) posits that both ICT and R&D have positive but independent effects on Total Factor Productivity (TFP), while Corrado, Haskel, & Jona-Lasinio (2017) argue that there is a relationship between ICT, R&D and innovation activities.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore not surprising that ICT has been proven to have a positive effect on economic growth (Khanna & Sharma, 2018;Sepehrdoust, 2018;Tolica et al, 2015). Even though many papers focus on the role of R&D and ICT separately, some authors argue that it is important to study the relationship and correlations between these two areas since they were shown to have complementary effects (Pieri et al, 2018;Khanna & Sharma, 2018;Mohnen et al, 2018). Many authors studying the factors affecting the growth of ICT sector agree that one of the key driving forces of ICT industry is R&D and innovation (Canarella & Miller, 2018;Lindmark et al, 2010;Manjón et al, 2016;Monge-Gonzálet & Hewitt, 2010;Stejskal et al, 2018;Tolica et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%